Ayurveda- A Guide To Prevent Life Style Diseases In Relation To Indriya Pradoshaja Vikaras w.s.r. To Nitya Sevaniya Ahara Dravyas - Chauhan, Chandani D; Vaghela, D B (International Research Journal of Ayurveda & Yoga, 2021)
Ayurveda– the science of life, deals with health promotion, prevention and management of disease. In Upanishada food is considered as Brahma. Acharya Charaka emphasizes importance of food as the body as well as diseases are formed by food. Wholesome and unwholesome food is responsible for happiness and misery respectively. Acharya Kashyapa quoted food as Mahabheshaja (supreme medicine). World Health Day is celebrated on 7th April, with WHO highlights the challenges & opportunities associated with food safety under the slogan “From farm to plate, make food safe” that indicates the importance of Ahara (food). Life styles disorders are a result of an inappropriate relationship of people with their environment. Indriyas (senses) are the media through which the objects of the external environment perceived and they reflect the ill health of body. Present paper highlights the importance of Ayurvedic dietetics and balanced nutrition as a preventive aspect of life style diseases in relation to Indriya Pradoshaja Vikaras (diseases related to sense organs) w. s. r. to Nitya Sevaniya Ahara Dravyas (wholesome daily foods). A conceptual analysis on the importance of it in day-to-day life.